A Review Paper on the Difference between Single-Cycle and Multi Cycle Processor (International Journal of Innovative Research in Computer Science & Technology, 2021)
The processors are all important  components of computer architecture. Computer  architecture is a specification that describes how  hardware and software technologies are connected to  create a computer platform. It refers to a system that  processes any fetched instruction. There are many  different types of processors, and we shall examine the  distinctions between single cycle and multi-cycle processors in this article. Former processors only  executed an instruction in a single clock cycle, while  multi-cycle processors disassembled the instructions into  multiple functional pieces and then executed each portion  in a separate clock cycle. Because the multicycle  processor breaks down each instruction into smaller  pieces, the amount of hardware required is decreased, and  several registers are added to store data that may be  utilized in the execution of subsequent instructions. A  multicycle processor executes instructions in smaller  clock cycles than a single cycle processor, according to  the proposed study.
Keywords: Arithmetic Logical Unit; Computer Architecture; Microprocessor; Multi-Cycle Processor